Assessment of static ejaculates of buffalo bulls for freezing and polyacrylamide gel migration - SINGH, SATWINDER; PANGAONKAR, G R; MATHAROO, J S; SHARMA, RAKESH (The Indian Journal of Animal Reproduction, 2023)
Study was conducted on assessment of static ejaculates of buffalo bull semen for freezing. The resultsrevealed significantly reduced freezing and PAG migration of static ejaculates.
Keywords: Static ejaculate; polyacrylamide gel migration; semen; spermatozoa; buffalo bull